The Role of Private Universities in Obtaining a Bachelor's Degree for Children with Special Needs - Sinaga, Dameria (Academy of Education Journal, 2025)
To improve achievement in the academic world, it must be centered on training programs. All lecturers must take part in training from the inclusive education service or certified institutions for students who are classified as having special needs. The curriculum is adjusted according to their specificities or the symptoms of students with special needs. learning facilities and infr astructure must also be provided that support the absorption of the learning. Purpose of this research. Researchers hope that everyone can be inspired or take the initiative to help children with special needs so that this program can be implemented. Special learning program for prospective students with special needs. Purpose of this research. Researchers hope that everyone can be inspired or take the initiative to help children with special needs so that this program can be implemented. Special learning program for prospective students with special needs. The method in this research uses qualitative research methods with a case study approach.